Applying the logistic regression for the quality of microelectronics product - Katemukda, Nichanach (Journal of Applied Statistics and Information Technology, 2021)
Nowadays Microelectronics is an important component to serve in many industries and the example of the microelectronic products are chip, microprocessor etc. According to the micro is too small then the root cause analysis is difficult, the factory in this case study found the crack on chip. They investigated and conclude the man machine and method are not the root cause of this symptom. The functional tester need to push down the product and the force that setting in the machine is fixed and every force pushing are reported. The report indicated no any variance of force pushing. One factor is the warps on substrate board that may cause of the crack on chip while the functional tester pushing the product during test. The binary logistic regression use to test a relationship between the chip crack and the warp of board. The statistical result indicated the warp of board between –21.480 to 10.253 Microns is not the cause the chip crack at 95% confident interval. Anyway the factory need to do further study with the chip supplier to verify on the root cause that suspect from raw material itself.